Transforming waste management practices among school children towards sustainable development through vermicomposting. - Esa, Norizan (Universiti Sains Malaysia, 2013)
Solid waste generation continues to rise and poses problems of disposal and management.There is therefore an urgent need to educate the public about waste reduction as a viable means of solid waste management. Exposing students to vermicomposting as a viable waste reduction activity become concrete experiences from which they learn about the benefits of waste reduction to the environment and promote this practice among themselves.